Coffee in the Age of Climate Change: Risks and Potential Impacts - Root Capital (2018)
This deck summarizes research on the impacts of climate change on coffee production in key Root Capital Root Capital geographies. The deck is designed as a reference document for a layman audience: staff of Root Capital and of peers in the Counsel for Smallholder Agricultural Finance (CSAF). The deck is a living document and will be updated periodically.